2020
DOI: 10.1186/s40648-020-00167-0
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on locomotion training via biomechanical models and a wearable haptic feedback system

Abstract: Locomotion is a fundamental human skill. Real-time sensing and feedback is a promising strategy for motion training to reconstruct healthy locomotion patterns lost due to aging or disease, and to prevent injuries. In this paper, we present a pilot study on locomotion training via biomechanical modeling and a wearable haptic feedback system. In addition, a novel simulation framework for motion tracking and analysis is introduced. This unified framework, implemented within the Unity environment, is used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Avoiding awkward postures is a common technique to prevent LBP, for example, Nelson et al [13] reported that nurses spend around 30% of their time performing forward bending or twisting. Furthermore, the impact that the haptic feedback had on our study aligns with the findings of Demircan [42], where he demonstrated that providing haptic feedback in real-time promotes motor learning.…”
Section: Discussionsupporting
confidence: 89%
“…Avoiding awkward postures is a common technique to prevent LBP, for example, Nelson et al [13] reported that nurses spend around 30% of their time performing forward bending or twisting. Furthermore, the impact that the haptic feedback had on our study aligns with the findings of Demircan [42], where he demonstrated that providing haptic feedback in real-time promotes motor learning.…”
Section: Discussionsupporting
confidence: 89%
“…These systems typically lack real-time feedback and there is still a clear emphasis on capturing data for analysis performed in hindsight, and the feedback is often limited to visual presentations in graphical form on a screen [ 65 , 66 , 67 ]. One exception is a pilot study on locomotion training where real-time haptic feedback was introduced [ 68 ]. Here vibrotactile actuators were used for immediate feedback on cadence and foot-drop angle during running.…”
Section: Introductionmentioning
confidence: 99%
“…For implementing the presented methodology in practice, subjects could be trained with haptic biofeedback to modify the FPA outside of the lab either on a treadmill or during straight line overground walking. In addition to FPA, several recent wearable haptic systems have been proposed for a variety of biomechanics applications [38]- [42], and thus it is feasible that the portable movement retention and cognitive demand findings presented here could potentially be expanded more generally to other movement parameters.…”
Section: Discussionmentioning
confidence: 99%